Ефект стохастичного резонананса при фільтрації звукових сигналів безпілотних літальних апаратів - Капуста, А. І. (ХНУРЕ, 2020)
Stochastic resonance should be understood as phenomena that occur in nonlinear systems in which when applied to a relatively weak noisy or subthreshold signal for detecting external noise, there is an increase in the signal-to-noise ratio or the probability of detecting and recognizing the signal. The amplification of the "useful" part of the output signal (signal / noise) depending on the intensity of the external noise is described by the dependence, which characterizes the term "resonance".
Keywords: БПЛА